Pengaruh Temperatur Anil terhadap Sifat Elektrokimia Lantanum Pentanikel (LaNi5) dengan Penambahan Serium Oksida (CeO2) - Ade Utami Hapsari; Jarot Raharjo; Yelvia Deni (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Annealing is one of the processes to increase capacity, discharge rate, and cycle life for anode AB5 type alloymaterial. Increasing the annealing temperature will increase capacity and homogenize material. This makesthe material more corrosion resistant and resistant to degradation during the process of absorption ordesorption of hydrogen atoms in the electrolyte solution. The study was conducted to see the characterizationof powders anode materials LaNi5 after the addition of 1% CeO2 and annealed at 300, 600, and 900°C for 6hours in an argon gas environment. The powders were characterized using XRD and SEM-EDX.Electrochemical testing is measured by using Electrochemical Impedance Spectroscopy (EIS) at a frequencyof 5 mHz - 100 kHz. Increasing anneal temperature changes the diffraction phase, decreasing conductivityand increasing the resistance value. Semicircle pattern of LaNi5 anode material with the addition of 1%CeO2 conducted annealing process shows the semicircle pattern with a radius of the arc increases. Thisindicates the magnitude of the resistance barrier material.